2021
DOI: 10.1136/bmj.n2132
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin and lung ultrasonography point-of-care testing to determine antibiotic prescription in patients with lower respiratory tract infection in primary care: pragmatic cluster randomised trial

Abstract: Objective To assess whether point-of care procalcitonin and lung ultrasonography can safely reduce unnecessary antibiotic treatment in patients with lower respiratory tract infections in primary care. Design Three group, pragmatic cluster randomised controlled trial from September 2018 to March 2020. Setting 60 Swiss general practices. Participants One general pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…PCT has emerged as a powerful biomarker for the early diagnosis of sepsis, blood stream infections and for monitoring infections to determine length of antibiotic treatment [12,13]. However, POCT PCT testing to determine antibiotic prescription in patients with lower respiratory tract infection in primary care in favor of AMS, as it is recommended by Lhopitallier et al [3], is likely not sufficiently sensitive to distinguish between pneumonia and other causes of LRTI in the outpatient setting. The mentioned study of Lhopitalier et al report on a cohort of patients with clinically diagnosed pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…PCT has emerged as a powerful biomarker for the early diagnosis of sepsis, blood stream infections and for monitoring infections to determine length of antibiotic treatment [12,13]. However, POCT PCT testing to determine antibiotic prescription in patients with lower respiratory tract infection in primary care in favor of AMS, as it is recommended by Lhopitallier et al [3], is likely not sufficiently sensitive to distinguish between pneumonia and other causes of LRTI in the outpatient setting. The mentioned study of Lhopitalier et al report on a cohort of patients with clinically diagnosed pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…This is a secondary analysis of a three-group cluster randomized trial which evaluated the impact of using procalcitonin and lung ultrasonography to reduce antibiotic prescriptions for clinical pneumonia in comparison to typical care across 60 primary care practices in Switzerland [ 13 ]. General practitioners included adult patients (aged 18 or over) presenting with clinical pneumonia as defined by the European guidelines for community-acquired pneumonia (an acute cough and at least one of the following: focal abnormal finding upon lung auscultation, dyspnea, tachypnea, or a history of fever > 4 days) between September 2018 and March 2020 [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…While data directly supporting PCT-guided antibiotic decision-making in outpatients with CAP are limited, one randomized trial comparing >150 outpatients with CAP found that clinical outcomes were similar and antibiotic exposure was decreased when PCT was used (107). A recent study evaluated 469 general practice patients with any kind of respiratory infections (108). Antibiotic use was reduced at a rate of 26% when PCT was used to guide antibiotic decision-making, while clinical outcomes were similar.…”
Section: Value Of Pct In Outpatient Follow-upmentioning
confidence: 99%